Analisis Mineral Matter dan Kualitas Batubara Blok Batulaki Kecamatan Satui, Kabupaten Tanah Bumbu, Provinsi Kalimantan Selatan (Jurnal Geomine, 2021)
Coal samples from Batulaki Block, Satui District, Tanah Bumbu Regency, South Kalimantan Province have been investigated on order to find out their mineralogical composition and quality. Mineral matter analyses were conducted using microscopic and X-ray diffractometry (XRD), whereas for coal quality analyses consist of proximate, total sulfur and calorific value. Results of mineral matters analysis show the coal samples dominated by kaolinite (Kln) which was followed by pyrite (Py), quartz (Qz), calcite (Cal) and goethite (Gt). The results of proximate, total sulfur, and calorific value analyses exhibit that coal quality of Batulaki block includes in high moisture, low ash, high volatile matter, medium fixed carbon and low sulphur. The average of calorific value is about 5516.94 cal/g indicating that coal rank of the Batulaki Block is classified as sub-bituminous coal.